Length and Diameter Ratio Effect on Gas Homogeneity Gradients Flow for Multi-Channel Carbon Filtration System Using Computational Fluid Dynamic Analysis - Mohd Sahri, Dzulkarnain; Zaini, Nabilah; Nasri, Noor Shawal; Mohd Zain, Husna; Mohamed Rashid, Norhana; Noor Shawal, Anis Shahirah (Journal of Advanced Research in Applied Mechanics, 2021)
Hazardous gases are the type of gases in which contributed negative impact to human health and environmental issue. Activated Carbon is the latest adsorption technology that can enhance hazardous gases capturing and applying to the industry applications. Carbon filtration is the device in which can control the concentration to hazardous gas before emitted to the surrounding. In order to increase gas mixing performance, L/D ratio concept was used for flow analyzing with helped of ANSYS Fluent Academic Version 19.2 Software. The optimization was carried out in the system with different inlet lengths to the system and throat diameters. The inlet lengths of 40, 65, 90 and 115 mm while throat diameters of 30, 40, 50, 60 and 70 mm were investigated. The static pressure of each cases was studied. As result, there are 10 cases in which mixed gas is uniformity inside the system. Maximum static pressure among these cases are 2600 Pa with inlet length and throat diameter of 40 mm and 30 mm respectively. As findings, different L/D ratio contributed to gas mixing performance as increasing carbon filtration performance in order to prolong lifespan, and preserve environmental quality.